ANALISIS KONTRIBUSI FAKTOR-FAKTOR PERTUMBUHAN EKONOMI KABUPATEN KLATEN - Haris, Abdul; Trisilo, Rismanto Gatot; Utami, Tri (Widya Dharma Journal of Business - WIJoB, 2022)
The purpose of this study was to determine the factors that influence economic growth in Klaten Regency. This type of research is descriptive qualitative or policy research. This research was conducted in Klaten district. The data sources of this research are primary and secondary data from Klaten district. Data analysis using the Klassen Method and regional disparities will be used using the Williamson Index calculation and Gini Index data. The results of this study based on the spatial aspect show that the use of agricultural land is still wide enough so that it is not worried about large-scale changes in land use and from the non-economic aspect that population growth is low but population density is high enough, TPAK and unemployment rates have decreased, HDI is equal to 74.79% shows a positive development and the condition of the poor in 2018 has also decreased.